Combination of green extraction techniques and essential oils to develop active packaging for improving the quality and shelf life for chicken meat - Marzlan, Anis Asyila; Meor Hussin, Anis Shobirin; Bourke, Paula; Chaple, Sonal; Barroug, Soukaina; Muhialdin, Belal J. (Taylor and Francis, 2021)
The poultry processing sector provides a sustainable source of animal protein of high nutritional quality. Plant essential oils were proposed as natural alternatives to enhance safety and extend the shelf life of poultry meat. However, the applications to this sector are limited due to the low stability and rapid oxidation of the essential oil. The emergence of active packaging incorporating essential oils has expanded potential food applications. Critical factors for successful development of active packaging interventions include appropriate essential oil selection, polymer source selection (carbohydrates-based, proteins-based), the bioactivity as a function of the packaging matrix as well as the target and food constituents, the minimum inhibition concentrations achievable in conjunction with processing conditions. The large gap between the commercially available active packaging and the demand for sustainable environmentally friendly packaging is an important limitation for current applications in chicken meat. Therefore, this article reviews the antimicrobial and antioxidant activity, the green extraction approaches and the applications of essential oils in controlled release packaging (CRP). Moreover, this review aims to fill gap between the CRP and their limitations to expand their potential applications in chicken meat.